2001
DOI: 10.1159/000056338
|View full text |Cite
|
Sign up to set email alerts
|

Scratching Behavior in Various Strains of Mice

Abstract: Scratching behavior was induced in 12 strains of mice and the frequency was compared. An injection of histamine at a dose of 50 nmol induced frequent scratching behavior only in ICR mice, although the same dose of serotonin induced frequent scratching behavior in all strains of mice except for A/J. Histamine (10 nmol), serotonin (1 nmol), substance P (50 nmol) and passive cutaneous anaphylaxis induced significant vascular permeability increase in BALB/c, ICR, ddY and NC/Nga mice. These four stimuli also induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
62
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 28 publications
15
62
0
Order By: Relevance
“…The scratching frequencies for the 60 min period for each inducer increased in a dose?dependent manner. These scratching agents more potently induced pruritic behaviors in ICR mice than in BALB/c mice, which are in agreement with a previous report (Inagaki et al, 2001). Particularly, compound 48/80 caused vigorous scratching behavior in ICR mice.…”
Section: Discussionsupporting
confidence: 92%
“…The scratching frequencies for the 60 min period for each inducer increased in a dose?dependent manner. These scratching agents more potently induced pruritic behaviors in ICR mice than in BALB/c mice, which are in agreement with a previous report (Inagaki et al, 2001). Particularly, compound 48/80 caused vigorous scratching behavior in ICR mice.…”
Section: Discussionsupporting
confidence: 92%
“…It produces a sensation of itch when applied to the human skin (Weisshaar et al, 1997) and has been suggested to be involved in the pruritus of polycythemia vera (Fjellner and Hagermark, 1979;Fitzsimons et al, 1981) and cholestasis (Schworer et al, 1995;Weisshaar et al, 1999;Jones and Bergasa, 2000). 5-HT has been used widely as a representative pruritogen in experimental models with rodents because it induces itchassociated scratching behavior when applied intradermally, regardless of strain differences (Inagaki et al, 2001). In contrast, intradermal histamine induces scratching behavior in only a few strains of mice (Inagaki et al, 2001) and induces little if any scratching in rats (Thomsen et al, 2001;Jinks and Carstens, 2002).…”
mentioning
confidence: 99%
“…5-HT has been used widely as a representative pruritogen in experimental models with rodents because it induces itchassociated scratching behavior when applied intradermally, regardless of strain differences (Inagaki et al, 2001). In contrast, intradermal histamine induces scratching behavior in only a few strains of mice (Inagaki et al, 2001) and induces little if any scratching in rats (Thomsen et al, 2001;Jinks and Carstens, 2002). Because a considerable amount of spontaneous scratching is observed in untreated naive mice, whereas naive rats exhibit little or no spontaneous scratching, the rat seems to be a suitable animal model to quantify acute pruritogen-evoked scratching behavior.…”
mentioning
confidence: 99%
“…Thus, we evaluated whether intradermal administration of not only histamine but also serotonin induces the scratching response in HR-1 mice and compared their responsiveness with those of ddY and ICR mice. Responsiveness to histamine was comparable in HR-1 and ICR mice, the latter of which are the most potent responders to histamine among the various strains (14). Serotonin induces moderate and severe scratching in ddY and ICR mice, respectively (14).…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, the scratching response to stimuli, especially to histamine, considerably differs among strains of mice (3,14). However, responsiveness of HR-1 mice to stimuli has not been reported.…”
Section: Discussionmentioning
confidence: 99%